2014
DOI: 10.1002/hep.26643
|View full text |Cite|
|
Sign up to set email alerts
|

Serum B-type natriuretic peptide in the initial workup of patients with new onset ascites: A diagnostic accuracy study

Abstract: Heart failure (HF) is, after cirrhosis, the second-most common cause of ascites. Serum B-type natriuretic peptide (BNP) plays an important role in the diagnosis of HF. Therefore, we hypothesized that BNP would be useful in the differential diagnosis of ascites. Consecutive patients with new onset ascites were prospectively enrolled in this crosssectional study. All patients had measurements of serum-ascites albumin gradient (SAAG), total protein concentration in ascitic fluid, serum, and ascites BNP. We enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 36 publications
0
55
0
1
Order By: Relevance
“…5 This pattern occurs because hepatic sinusoids are normally permeable in heart failure–related ascites, which allows for leakage of protein-rich lymph into the abdominal cavity. 7,9 In cirrhosis, hepatic sinusoids are less permeable due to fibrous tissue deposition, resulting in ascites with low protein content. 7,9 Nevertheless, this patient likely also has some liver fibrosis due to long-standing congestive hepatopathy.…”
Section: Application Of Test Results To This Patientmentioning
confidence: 99%
See 2 more Smart Citations
“…5 This pattern occurs because hepatic sinusoids are normally permeable in heart failure–related ascites, which allows for leakage of protein-rich lymph into the abdominal cavity. 7,9 In cirrhosis, hepatic sinusoids are less permeable due to fibrous tissue deposition, resulting in ascites with low protein content. 7,9 Nevertheless, this patient likely also has some liver fibrosis due to long-standing congestive hepatopathy.…”
Section: Application Of Test Results To This Patientmentioning
confidence: 99%
“…7,9 In cirrhosis, hepatic sinusoids are less permeable due to fibrous tissue deposition, resulting in ascites with low protein content. 7,9 Nevertheless, this patient likely also has some liver fibrosis due to long-standing congestive hepatopathy. Her anemia and thrombocytopenia are predominantly due to splenomegaly.…”
Section: Application Of Test Results To This Patientmentioning
confidence: 99%
See 1 more Smart Citation
“…Rivalta test was developed in 1895 by the Italian physician Fabio Rivalta and is widely used as a marker for the differentiation between exudates and transudates in human body cavity effusions. 3,[8][9][10] Previous studies demonstrated that most cases of cardiac ascites with high AFTP (≥ 25 g/L) were incorrectly considered to have an AFTP less than 25 g/L. Previous study demonstrated that quantitative analysis of AFTP had diagnostic accuracy of 88%.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Samples are categorized as transudates, if the AFTP is less than 25 g/L and as exudates if AFTP is greater than 25 g/L. 3, 10 Gupta et al reported that 24% of patients with uncomplicated cirrhosis had an AFTP concentration greater than 25 g/L, 8 and Alexandrakis et al reported that 20% of malignant ascites had a low AFTP concentration (< 25 g/L). 8 Thus, some clinical practice guidelines recommend that AFTP concentration should be determined in the initial laboratory investigation of ascitic fluid.…”
Section: Introductionmentioning
confidence: 99%